Hérnia umbilical em bezerro - Sousa, Lara Luiza Fontinele (Universidade Federal do Tocantins, 2022)
This report describes the activities developed during the Supervised Curricular Internship, carried out at the city of Brejo Grande do Araguaia (PA), following the routine of veterinarian Rodrigo Rodrigues, who was the supervisor of this internship, and works in the field, in the area of clinic, surgery and reproduction of cattle. The internship period was from January 19, 2021 to April 1, 2021, with a workload of 40 hours per week, totaling 416 hours. Among the cases monitored, the highlights were the care aimed at animal reproduction, however, cases of mastitis, rectal prolapse, suspicion of worms, suspicion of polioencephalomalacia and acrobustitis were also attended. Among the surgical cases, there was an umbilical hernia in a calf, mixed breed, with 2 months of age, being the case of interest in this work. In this case, surgical treatment was performed, accomplishing herniorrhaphy, which was successfully performed and allowed the complete recovery of the animal after 11 days after surgery, when the stitches were removed.